A04 Contrasting Urban Contexts in Healthy Ageing: The case of Luxembourg urban agglomeration. Issue 2 (June 2015) - Koeppen, Bernhard; Chaix, Basile; Gerber, Philippe; Kestens, Yan; Klein, Olivier; Klein, Sylvain
Abstract: Background: Various epidemiological studies give strong evidence that social integration, physical activity and mobility are favourable for healthy ageing. The more mobile and socially integrated elder individuals are the better is their health compared to others in the same cohort of age. When it comes to critical assessment of accessibility and tangible barriers or obstacles for everyday mobility and physical activity in (urban) environment(s), numerous studies in the fields of urbanism, geography, planning studies as well as architecture and even social sciences do exist. With an ageing population as important challenge for most Western societies, it is not very surprising though, that the identification of potential obstacles and barriers to mobility and social activities, which are not related to pathological issues, is an important task for research and practitioners in order to increase public health and the well-being of elder individuals. Some components of healthy aging including physical activity, social participation or mobility have been linked to dimensions of the built environment, but a more profound understanding. of the processes linking environments to health among older adults is still lacking. Methods: The international, multidisciplinary project "Contrasting Urban Contexts in Healthy Ageing" goes beyond the compilation and combination of the results from separate studies, but collects and analyses detailed data on daily mobility and health outcomes among older adults in contrasted urban settings in Montreal, Paris and Luxembourg. The proposed paper will present first results from Luxembourg, where a "classical" quantitative survey dealing with well-being, health, mobility and the perceived environs has been combined with the collection of GPS-data and data on physical activity (accelerometer) during 7 days with 500 persons aged 65 and older. As this approach does take into consideration demographic characteristics as well as spatial qualities, an innovative, unique and robust strategy for socio-spatial sampling had been developed and applied. Results: The study shows that – as expected - serious health issues do affect mobility behavior (and vice versa). Nonetheless, confirmed habits tend to be very stable. Furthermore, the general character as well as the attachment to the neighbourhood can play a certain role. Conclusions: The analysis of the first batch of data proves that the multidisciplinary perspective and integrated empirical approach does deliver new, reliable information on how characteristics of urban environments relate to the crucial dimensions of healthy aging and mobility behaviour.